2018
DOI: 10.1080/23322039.2018.1453574
|View full text |Cite
|
Sign up to set email alerts
|

On intellectual capital and financial performances of banks in Malaysia

Abstract: The purpose of the study is to consider and measure the intellectual capital towards the financial performances of the local banks in Malaysia. The study will implement the Value Added Intellectual Coefficient (VAIC) method to evaluate the financial performances of the ten local banks in Malaysia. The study will determine how the intellectual capital influences the financial performances of banks in terms of two periods which are latest six years from 2011 to 2016 and the past ten years from 2007 to 2016. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
93
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 39 publications
13
93
1
4
Order By: Relevance
“…Firer and Williams [1] also emphasized the importance of PC in improving the sustainable performance of an institution. However, previously, many studies reported the positive impact of CEE on performance [4,6,12,18,[32][33][34]39,41,52,58,63,67,71,75,77], while some reported no relationship between CEE and performance [1,10,35,37,38,43]. We thus, pose the following hypothesis:…”
Section: Cee and Performancementioning
confidence: 76%
See 4 more Smart Citations
“…Firer and Williams [1] also emphasized the importance of PC in improving the sustainable performance of an institution. However, previously, many studies reported the positive impact of CEE on performance [4,6,12,18,[32][33][34]39,41,52,58,63,67,71,75,77], while some reported no relationship between CEE and performance [1,10,35,37,38,43]. We thus, pose the following hypothesis:…”
Section: Cee and Performancementioning
confidence: 76%
“…However, the literature about examining the impact of IC on the performance of financial institutions is limited to an extent. Many researchers used VAIC and reported the positive impact of IC on the performance of the financial sector in different countries [4,6,10,12,28,30,31,33,35,39,40,45,52,[68][69][70][71][72][73][74]. For instance, using a sample of 38 Indian banks over the period 2005-2016, Vidyarthi [40] applied Tobit regression and found a positive impact of both IC measures, i.e., VAIC, MVAIC, and their component, i.e., HCE, on efficiency.…”
Section: Ic and Performance Of Financial Institutionsmentioning
confidence: 99%
See 3 more Smart Citations